Asymmetries in the Responses of Sub-Central Governments to Changes in Grants: Evidence From an Event Study - Julia Darby; Anton Muscatelli; Graeme Roy (European Regional Science Association (ERSA), 2006)
In this paper we examine how sub-central governments respond to significant changes in their grant allocations. We focus on the reactions of State, Regional and Local governments in fifteen countries over a period of 20 to 30 years to significant exogenous increases and decreases in their grant allocations. We observe that when grants are cut, sub-central governments respond by cutting spending on their wage bill and, disproportionately, on capital expenditure. Therefore, while centrally imposed cuts do result in expenditure restraint at the sub-central level, the composition of the adjustment appears to suffer from short-termism. In addition, our results suggest that sub-central politicians seek to further defend current spending programs by significantly increasing local/regional taxation. In contrast, during periods of significant expansions in grants, these revenues remain constant with the full extent of the grants increase passed on to current expenditures. Taken together these two results imply a kind of asymmetric 'fly-paper' effect. Finally, we trace the different responses of governments according to their degree of expenditure decentralisation and tax and borrowing autonomy.
Keywords: 330